(untitled) (Research, Society and Development, 2021)
Human milk has a balance of nutrients and bioactive compounds, and it must be the exclusive food source during the first six months of the infant’s life. In cases where the woman is unable to breastfeed, due to hypogalactia or pre-existing disease, the use of donated human milk, available in human milk banks, is recommended. Currently, in the human milk banks the processing applied for greater conservation is Holder pasteurization. Therefore, the objective of this work is to perform a search in the literature about new possible treatments to be applied to human milk, and its influence on its physical-chemical composition; and in this sense, the studied processes were: Holder pasteurization, lyophilization, spray-drying, high hydrostatic pressure, high temperature and short time, and short wave ultraviolet irradiation. For that, a search was performed in databases, and 126 articles were selected to carry out this review according to the keywords used. It was observed that the studied treatments can be applied for the processing and conservation of human milk, once it was applied in matrices with similar composition.